2007
DOI: 10.1590/s0004-282x2007000100015
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic subdural hygroma: five cases with changed density and spontaneous resolution

Abstract: -Thirty-four consecutive adult patients with subdural traumatic hygroma were analysed for clinical evolution, serial computed tomography scan (CT), and magnetic resonance imaging (MRI) over a period of several months. Five of the patients presented CT scan and MRI evolution data showing increasing density over a period of 11 days to 6 months post trauma. In these five patients, final clinical and CT scan data were benign, with complete spontaneous resolution. Descriptions in literature of evolving traumatic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…92% of patients who have undergone DC harbor the TSH ipsilateral to the surgery side. [1019232427] High dynamic accidents and diffuse traumatic brain injuries have been pointed out as risk factors for a subdural hygroma (SDG) following DC. [68101216182325] On the other hand, duraplasty at the time of DC has been observed to lower the incidence of TSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…92% of patients who have undergone DC harbor the TSH ipsilateral to the surgery side. [1019232427] High dynamic accidents and diffuse traumatic brain injuries have been pointed out as risk factors for a subdural hygroma (SDG) following DC. [68101216182325] On the other hand, duraplasty at the time of DC has been observed to lower the incidence of TSH.…”
Section: Discussionmentioning
confidence: 99%
“…proposed a new classification of TSH according to the presence of mass effect and hydrocephalus. [2627] They divided TSH into group I without mass effect, and II with mass effect. A subdivision was made in group I into Ia without hydrocephalus, and Ib with hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas patients with mild and moderate GCS showed good recovery (19/22 patients, 86%) regardless of type of management they had (Table 4). Many authors reported similar results with a high percentage of good outcome in patients with mild and moderate Glasgow Coma Score [11] [21] [24]. Other factors as age, gender, site of SDHy or associated pathology had not yet reached a statistical significant value in determining the clinical outcome or even the type of management of patients with subdural hygroma.…”
Section: Discussionmentioning
confidence: 91%
“…Some investigators indicated that conservative methods is the appropriate one for its spontaneous resolution (5,8,19). Others suggested that surgical procedure is necessary for the complications of mass effect and it can relieve patients' suffering immediately (2,16).…”
Section: █ Resultsmentioning
confidence: 99%
“…Poor prognosis appears when mass effect, serious brain injury or intracranial hematoma occur, and the mortality is high (1,2,4). █ InTRODuCTIOn T raumatic subdural effusion is a common disease, and has a high percentage in traumatic head injury cases (2,4,7,12,19,20). Traumatic subdural effusion occurs AIm: Traumatic subdural effusion (TSE) occurs following traumatic brain injury and may be treated by either conservative methods or surgical procedure commonly according to the patients' clinical information.…”
Section: Introductionmentioning
confidence: 99%